Impact of climate change on the spread of infectious diseases - review - Lecka, Martyna; Omyła, Małgorzata; Pietryszak, Edyta; Paruzel, Marcel (Journal of Education, Health and Sport, 2025)
Advances in sanitation, broader access to healthcare, and developments in preventive and clinical medicine have contributed to reducing mortality and morbidity from many infectious diseases. Nevertheless, recent outbreaks of emerging infectious diseases (EIDs) have caused significant health losses, and their frequency is likely to increase due to the impact of climate change on pathogens, the environment, and populations. Extreme or prolonged changes in temperature, precipitation, humidity, and air pollution resulting from climate change can, for example, expand the range of EID reservoirs, increase host–pathogen and cross-species interactions, and degrade the health of susceptible populations, thereby promoting new EID outbreaks. It is therefore crucial to establish global strategies for tracking and modeling potential EID responses to predict their future behavior and guide research on early detection, diagnostics, and vaccine development. Multi-disciplinary, intercontinental collaborations are essential to develop effective surveillance and modeling platforms that leverage artificial intelligence to mitigate the effects of climate change on EID outbreaks. In this article I discuss how climate change elevates the risk of EIDs, present novel approaches to enhancing the surveillance of emerging pathogens that pose epidemic threats, analyze both existing and new measures to contain or reduce the risk of future EID outbreaks, and describe advanced methods for tracking EIDs during outbreaks to limit their transmission.